Prevalence of thrombocytopenia, anti–platelet factor 4 antibodies and D‐dimer elevation in Thai people After ChAdOx1 nCoV‐19 vaccination - Noppacharn Uaprasert; Phandee Watanaboonyongcharoen; Rattaporn Vichitratchaneekorn; Sasinipa Trithiphen; Benjaporn Akkawat; Autcharaporn Sukperm; Thanisa Tongbai; Watsamon Jantarabenjakul; Leilani Paitoonpong; Ponlapat Rojnuckarin (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Vaccine‐induced immune thrombotic thrombocytopenia (VITT) is a rare distinctive syndrome characterized by unusual site thrombosis accompanied by thrombocytopenia after ChAdOx1 nCoV‐19 vaccination. Platelet‐activating anti–platelet factor 4–dependent antibodies (anti‐PF4 Abs) were detected in most cases of VITT. To date, data from Asian countries are lacking. Objectives To determine the prevalence of thrombocytopenia, anti‐PF4 Abs, and D‐dimer elevation in Thai people administered the ChAdOx1 vaccine. Patients/Methods A total of 521 vaccinated and 146 nonvaccinated subjects were enrolled. Blood samples were collected to determine platelet counts, anti‐PF4 Abs using ELISA and D‐dimer levels 5 to 30 days after the first vaccination. Results None of the participants developed thrombocytopenia or had significantly decreased platelet counts from baseline after ChAdOx1 vaccination. The frequencies of anti‐PF4 Abs between vaccinated (16/521; 3.1%; 95% confidence interval [CI], 1.8‐4.9) and nonvaccinated Thai people (6/146; 4.1%; 95% CI, 1.5‐8.7) were similar. None of the detectable anti‐PF4 Abs activated platelets in vitro. The average D‐dimer levels between vaccinated and control groups were similar (282.2 ± 286.3 vs 267.8 ± 219.3 ng/mL; P = 0.58). Four vaccinated and one nonvaccinated participants had markedly elevated D‐dimer levels >2000 ng/mL without detectable anti‐PF4 Abs. Imaging studies of these asymptomatic subjects revealed incidental pulmonary embolism in a vaccinated elderly woman. Conclusions This study demonstrated a low prevalence of thrombocytopenia and pathogenic anti‐PF4 Abs after ChAdOx1 vaccination. D‐dimer testing revealed no significant coagulation activation. Routine tests for platelet counts, anti‐PF4 Abs, and D‐dimer levels are not recommended for VITT screening without clinical suspicion.